Juridical Review of Wills That Do Not Meet Portie Legitieme in Civil Inheritance Law (Study of High Court Ruling Number 86/PDT/2017/PT PAL) - Jesica; Tjempaka (Dinasti Research, 2024)
The purpose of this research was to find out how the law views whether a will is valid or not which reduces the share of the inheritance (legitieme portie) of the rightful heirs and to find out the judge's considerations in determining the distribution of inheritance in the Palu High Court decision number 86/PDT/2017/ PT PAL. This research uses a normative-empirical juridical research method with a statutory approach, uses secondary data types with data collection techniques, namely interviews, document studies, and case studies, and uses legal analysis data collection techniques. A person can obtain his inheritance through 2 (two) ways according to civil inheritance law, namely according to the provisions of the law and a will. A will is a statement about what is desired to happen after the person dies and can be revoked by it. If during their lifetime the testator has made a will, then before calculating their respective inheritance shares, they must also pay attention to the existence of the legitimate portie or absolute share of the heir.